High survival promotes bunchgrass persistence in old‐growth savannas under different fire regimes - Jennifer M. Fill; Raelene M. Crandall (Ecosphere)
Abstract Clonal perennial grasses are a key functional group in fire‐prone, old‐growth grasslands and savannas. They are flammable and can resist extinction for decades. Although clonal grasses as a functional group are considered resilient to fire regime variation, data‐based research on clonal grass dynamics under multiple different fire regimes is still lacking. We modeled the population dynamics of wiregrass (Aristida beyrichiana), an endemic perennial bunchgrass, under very different long‐term, frequent fire regimes within the historical range of variation, in two southeastern US pine savanna environments. All wiregrass populations had similar and stable population growth rates. As expected for a long‐lived species, survival was nearly 100% in all populations. Given that flowering in wiregrass is fire‐stimulated, there was high variability in flowering and seed production between fire and non‐fire years. The consistency of results between our study populations lends data‐driven support to wiregrass' resilience under fire regimes that differ in frequency and seasonality. The patterns we observed in wiregrass mirror inferences from other studies of dominant grass dynamics in old‐growth tropical savannas and support the inclusion of old‐growth US pine savannas in global savanna ecology.